Evaluación al sistema de control interno de la empresa Comestibles del Quindío Kopla S.A.S (2012)
evaluation system of internal control in the FOOD COMPANY OF QUINDIO KOPLA SAS, was performed by applying the latest auditing standards on internal control processes through which they make a diagnostic to determine if controls used by the company are provide adequate and whether the expected effectiveness.